Carro Triumphal: Pizarro, Genres and Jewish Historiography in 17th c. Amsterdam - Gutwirth, Eleazar (Meldar: Revista internacional de estudios sefardíes, 2020)
In this article there is an attempt to offer a new reading of the work entitled Cesáreo carro triumphal: En que gloriosamente campean por el orbe las invencibles armas del Maximo Emperador Leopoldo I. de este nombre, por la feliz restauración de la real fortaleza de Buda, conquistada en 2 de sept. de 1686 by Antonio Pizarro de Oliveros. Its components paratexts and ideas are analyzed. An historical and historiographic context is reconstructed to help in its comprehension.